Explaining the WAEMU Growth Spurt : The Role of Financial Deepening and Macro Policy - Haile, Fiseha; Moller, Lars Christian (World Bank, Washington, DC, 2018)
Most countries of the West African Economic and Monetary Union (WAEMU) experienced a growth acceleration in 2011-17. This paper identifies the determinants of this growth by combining country-specific information with the results of a cross-country regression model. Growth was characterized by capital accumulation and driven by structural factors, including financial deepening and infrastructure development. What sets WAEMU countries apart from other African countries is the very sharp increase in private sector credit supporting private investment. This was facilitated by a prudent and accommodative regional monetary policy and improved financial regulation. Pro-cyclical fiscal policies supported public infrastructure investment but led to a buildup of public debt. Going forward, growth may lose some steam, given the renewed policy emphasis on fiscal consolidation and monetary tightening.